Pengaruh Variasi Komposisi Aerogel Silika Terhadap Sifat Fisis Pada Pembuatan Biofoam - Chandra Gumilang; Roniyus Marjunus; Agus Riyanto; Sutiarno (Jurnal Teori dan Aplikasi Fisika, 2026)
Biofoam is a type of bioplastic that can be used as an alternative packaging product to replace styrofoam. Biofoam still has a high value of water absorption, so silica aerogel is added as a hydrophobic agent. The purpose of this study was to determine the effect of adding silica aerogel to the functional groups of biofoam, crystal structure, density and water absorption. The method used in this research is thermopressing. The thermopressing method is a method where all the ingredients, started from fiber, starch, silica aerogel and PVA, were mixed to form a dough and then pressed for 3 minutes at 150℃ using a thermopressing tool. In relation to the characteristic results obtained from the FTIR analysis, it was found the presence of silica aerogel functional groups at wave numbers 1058.60 cm-1 and 925.83 cm-1. Apart from silica, the functional groups of cellulose and starch are also found. Furthermore, the results of the crystal structure analysis found silica and cellulose phases with different phase weight percent values. Where the weight percent of the phase for silica increases and the weight percent for the cellulose phase decreases with the addition of silica composition. The results of the physical density test showed that the density value decreased with increasing silica composition. The results of the analysis of water absorption show that the value of water absorption increases with increasing silica composition, this is because silica has morphological properties in the form of an ultraporous solid material that is able to absorb more water, and the phase separation method is not carried out on silica to obtain silica. with high hydrophobic properties. Keywords: Biofoam, silica airgel, water absorption